Henny Penny - Galdone, Paul. (New York : Clarion Books, 1968)
Henny Penny and her friends are on the way to tell the king the sky is falling when they are outwitted by the fox.
Adaptation of: Chicken Licken.
Book Links (A.L.A.)
Elem. School Library Collection
Wilson's Children
3.4
K-3
Keywords: Animals -- Folklore; Fairy tales; Folklore; Animals -- Folklore; Fairy tales; Folklore